The damage from clean floats: From an anti-inflationary monetary policy - Robin Pope; Reinhard Selten; Johannes Kaiser; Sebastian Kube; Jürgen von Hagen (University of Bonn, Bonn Graduate School of Economics (BGSE), 2007)
The paper traces the dangers in the closed economy perspective of a monetary policy focused on a domestic inflation goal under a clean float. Field evidence of the damage wrought from this perspective is reinforced by that from a laboratory experiment. The laboratory experiment avoids measurement errors to which econometric estimation is subject concerning omitted or inadequately proxied determinants, non-normally distributed errors, inadequate degrees of freedom, false assumptions of temporal independence and false synchronicity in decision response lags to stimuli. Our laboratory experiment also embeds a new theory of exchange rate determination involving the uncontroversial power of fully cooperating central banks to totally fix the exchange rate. The new model is within a broader theory that includes risk effects normally excluded, SKAT, the Stages of Knowledge Ahead Theory. We use SKAT to analyse outliers in our experimental results, and indicate some new directions and foci for econometric work. Our laboratory results point to the superiority of dollarisation, currency unions, a single world money over even dirty floats that include the exchange rate as an objective in its own right.
Keywords: D80; F31; 330; outliers analysis; clean float; dirty float; IMF; exchange rate regime; exchange rate volatility; experiment; SKAT the Stages of Knowledge Ahead Theory; monetary policy; transparent policy; exchange rate shocks; central bank cooperation; central bank conflict; beggar thy neighbor; Flexibler Wechselkurs; Wechselkurssystem; Inflationsbekämpfung; Offene Volkswirtschaft; Wechselkurstheorie; Test; Internationale Währungspolitik; Theorie